Failure modes, effects, and diagnostic analysis (FMEDA) of ESD Valves in oil and gas industry - Bensmaine, Omar; Naït-Saïd, Rachid; Fatiha Zidani (1st Asia Pacific Industrial Engineering and and Operations Management Conference virtually, July 9-11, 2021)
The Safety Instrumented System (SIS) is an automated system used to implement one or more safety instrumented functions. A SIS, like the Emergency Shutdown (ESD) system, consists of any combination of sensor(s), safety PLC(s) and final element(s) (e.g. ESD valves). ESD valves are the last line of defense against risks, although the ESD valve has high performance, the data (based on expert judgment and OREDA database) indicates that ESD valves failures are the most critical in the ESD systems. In order to improve the reliability and safety of these valves, we applied the FMEDA diagnostic technique. We started with a decomposition of the ESD valve to the subsystems and we identified their functions. Then we described the failure modes, their mechanisms, their sites and their effects. Then we identified the impact of each failure mode according to the criticality classes and identified the failure rates and their class according to the criticality and the detectability by automatic diagnosis of each mode and from the failure rates we calculated the Safe Failure Fraction (SFF) and Safety Integrity Level (SIL) required and we concluded that the actuator subsystem is the most critical system. Finally, we proposed preventive and protective measures to eliminate or reduce the risk of failure.